Alpha Cells, The Main Source of IL-1β in Human Pancreas - Anquetil, Florence (J Autoimmun, 2017)
Interleukin-1β (IL-1β) is known to trigger beta cell dysfunction in vitro and could potentially play a role during the pathogenesis of type 1 diabetes and type 2 diabetes. However, several clinical trials attempting to block IL-1β function have had minimal success. We therefore reinvestigated local expression of IL-1β in human diabetic and non-diabetic pancreata. We obtained pancreatic tissue sections from the Network for Pancreatic Organ Donors with Diabetes (nPOD) including non-diabetic control (n=9), non-diabetic auto-antibody positive (AAb+, n=5), type 1 diabetes (n=6), and type 2 diabetes (n=6) donors. Islets were systematically investigated for the presence of IL-1β mRNA by in situ hybridization and IL-1β protein by indirect immunofluorescence. We found that intra-islet IL-1β was produced at comparable levels in both non-diabetic and diabetic donors. Interestingly, the main source for IL-1β was alpha cells but not beta cells. Our findings call into question the role of IL-1β in the diabetic pancreas as it has been proposed in previous literature. Additionally, our results regarding the localization of IL-1β should lead to further investigation into the role of IL-1β in the physiology of pancreatic alpha cells.